Evaluation of the potential aphrodisiac activity of sesquiterpenoids from roots of Ferula huber-morathii Peşmen in male rats. (15th July 2020) - Aydogan, Fadime; Baykan, Sura; Soliman, Gamal A.; Yusufoglu, Hasan; Bedir, Erdal
Abstract: Ethnopharmacological relevance: Several species of Ferula L. genus have been used in traditional Turkish medicine as aphrodisiac to treat male sexual dysfunction. Especially, roots and oleo gum resin of F. elaeochytris Korovin, F. communis L., F. assa-foetida L. and F. gummosa Boiss. were claimed to be used for aphrodisiac activity, menstrual regulation and treatment of gastric pain in Anatolia. Ferula L. is represented by 23 taxa in Turkey, 13 of which are endemic species. F. huber-morathii Peşmen (FHM), an endemic plant, is popularly known as ''helizan, çağşır''. Aim of the study: This study aimed to isolate sesquiterpenoids from the roots of Ferula huber-morathii (FHM) and to confirm their aphrodisiac potential in male rats. Material and methods: In a preliminary experiment, the effects of aqueous (H2 O) and chloroform (CHCl3 ) extracts of FHM were tested for their potential aphrodisiac activities in male rats. Then, sesquiterpene derivatives were isolated from the active chloroform extract of FHM roots (FHM-R) and characterized (TLC, 1D, 2D NMR, HR-MS and CD). Moreover, some of the isolates with adequate quantities were evaluated for their possible aphrodisiac effects on male rats. Single doses (10 mg/kg BW) of sildenafil citrate (SC, positive control), gummosin, mogoltavidin, deacetylkellerin, ferukrin acetate with kellerin, elaeochytrin-A and ferutinin were administered orally by gavages to male Wistar albino rats. Mount latency (ML), mount frequency (MF), intromission latency (IL), intromission frequency (IF), ejaculation latency (EL) and postejaculatory interval (PEI) were studied. In addition, copulatory efficiency (CE) and intercopulatory efficiency (ICE) were calculated. Results: The preliminary experiment revealed that the chloroform extract was the main source of the active compounds as it showed the higher aphrodisiac activity while the aqueous extract was found to be inactive. Eleven sesquiterpene derivatives, viz. gummosin, mogoltavidin, farnesiferol A, deacetylkellerin, ferukrin acetate, kellerin, teuclatriol, feruhermonin C, ferutinin, elaeochytrin A and teferidin, were isolated from the FHM-CHCl3 extract. Oral administration of deacetylkellerin, elaeochytrin-A and ferutinin significantly increased MF and IF. The ML and IL were significantly reduced, and ejaculation latencies were prolonged. Administration of these sesquiterpenoids also reduced the PEI. The present results revealed that ferutinin was the most effective aphrodisiac compound compared to other sesquiterpenoids. The results of 10 mg/kg of ferutinin are comparable to SC, the positive control. The results revealed that gummosin, mogoltavidin and ferukrin acetate with kellerin did not significantly alter the aphrodisiac parameters. Conclusions: This study has established that the CHCl3 extract of FHM root contains sesquiterpene derivatives, especially coumarin ethers and benzoic esters. Findings of the present study demonstrate that the chloroform extract and some of the sesquiterpene derivatives significantly stimulates sexual behavior in male rats, thus suggesting that F. huber-morathii possesses an aphrodisiac activity. Graphical abstract: Image 1